Change by Design: How Design Thinking Transforms Organizations and Ins pires Innovation - Brown, Tim (HarperBusiness, 2009)
The myth of innovation is that brilliant ideas leap fully formed from the minds of geniuses. The reality is that most innovations come from a process of rigorous examination through which great ideas are identi fied and developed before being realized as new offerings and capabili ties. This book introduces the idea of design thinking‚ the collaborat ive process by which the designer's sensibilities and methods are empl oyed to match people's needs not only with what is technically feasibl e and a viable business strategy. In short‚ design thinking converts n eed into demand. It's a human-centered approach to problem solving tha t helps people and organizations become more innovative and more creat ive. Design thinking is not just applicable to so-called creative indu stries or people who work in the design field. It's a methodology that has been used by organizations such as Kaiser Permanente to increase the quality of patient care by re-examining the ways that their nurses manage shift change‚ or Kraft to rethink supply chain management. Thi s is not a book by designers for designers; this is a book for creativ e leaders seeking to infuse design thinking into every level of an org anization‚ product‚ or service to drive new alternatives for business and society.
Keywords: IMPORTANT